Analysis of the Effect Using Financial Ratios, Ownership and Corporate Size on Corporate Value in Food and Beverage Corporate - Putu Kepramareni; Sagung Oka Pradnyawati; Komang Ayu Muliahati (International Journal of Applied Business and International Management, 2023)
The food and beverage industry experienced a decline in share prices in the 2018-2020 period. The stock price is an indicator in considering investment steps and is used as a reflection of the corporate's value. This research is causality with the main objective of obtaining empirical evidence related to the impact of several financial ratios, the size of a corporate and ownership factors on the high or low corporate value by using the subjects of the consumer goods sector which experience a significant decline in stock prices every year. The author uses financial ratio analysis, ownership and impact on corporate size in influencing the formation of corporate value. The authors found that financial ratios (liquidity and profitability) form a positive relationship to corporate value in contrast to leverage, managerial ownership, institutions and corporate size which do not show any significant effect on corporate value These findings add empirical evidence to the variables tested on their effect on corporate value.Â Keywords: Leverage, Liquidity, Profitability, Managerial Ownership, Institutional Ownership, Corporate Size, Corporate Value